EDUCATING GOOD MORAL VALUES THROUGH VIDEO GAME: HARVEST MOON BACK TO NATURE PERSPECTIVES - Syahputra, Fikry Prastya; Albar, Mahmud Arief (UI Scholars Hub, 2023)
Globalization makes cultural absorption faster, but this also has a negative effect if the culture exposed is unsuitable. This will also affect the morale of a generation. One media that can spread culture and moral values is video games. For example, in a role-playing game genre which makes the players act like it is their real life, they can grasp many valuable experiences. Therefore, this study aims to identify the moral values in a video game called Harvest Moon: Back to Nature. Harvest Moon: Back to Nature or HM BTN is a role-playing game in which the player acts as an amateur farmer to save his inheritance farm. The data in this study is in the form of text and co-text derived from the game. This study applies qualitative descriptive methods to analyse and present the results. The analysis results demonstrate that seven types of moral values were identified from the video game. They are; bravery, love and affection, sympathy to others, cooperativeness, thankfulness, trustworthiness, and kind-hearted. This result indicated that Harvest Moon: Back to Nature video game presents not only entertaining gameplay to the gamers but also several moral values that construct a good personality to them. It can be concluded that video games can be utilized as learning media depending on the genre and theme. Educators need to select the appropriate one.